Spatial Distribution of Exhalation Droplets in the Bus in Different Seasons - Wenzhu Duan; Dan Mei; Jiaqian Li; Zihan Liu; Mengfan Jia; Shanshan Hou (Aerosol and Air Quality Research)
Abstract In closed buses, the spread of droplets with viruses/bacteria may cause the spread of respiratory infectious diseases. Discrete phase modeling is used to simulate the diffusion characteristics and concentration distribution of droplets at different temperatures and different exhalation positions by ANSYS FLUENT software. The integral concentration of droplets at different locations can be quantified, which leads to identification of low-risk areas and high-risk areas in the bus. Results show that a higher outdoor temperature leads to lower droplets’ diffusion speed and longer time until the droplets reach the driver. In addition, based on the integral concentration of droplets at the seats, regardless of whether a passenger exhales droplets in the front row of the bus, the position of the rear door or the last row of the bus, the seats in the last row of the bus away from the door belong to the low-risk area. In contrast, the seats near the door and the middle seat in the bus are higher risk areas. Consequently, this study proposed sitting on a seat in the low-risk area as a means to reduce the risk of passengers. Moreover, safety protection facilities around the driver should be modified to improve the isolation of the upper area of the driver’s location, so as to effectively prevent the droplet diffusion towards the driver, thereby effectively reducing the driver’s risk of infection.